Ein Beitrag zur Steuerung der Faserstaubentwicklung faserverstärkter Kunststoffe beim mechanischen Recycling - Tölle, Lisa

Mesh‐ and model adaptivity for NTFA and full‐field elasto‐plastic homogenization based on downwind and upwind approximations - Tchomgue Simeu, Arnold; Mahnken, Rolf (PAMM)
Abstract To increase the quality of computational results for heterogeneous materials like fiber‐reinforced composites with Prandtl–Reuss‐type material laws, goal‐oriented measures of the adaptive finite element method coupled to model adaptivity is established. The former is an adaptive mesh refinement on the macroscale, which allows to control the spatial discretization errors. The latter is an efficient combination of a numerically low cost nonuniform transformation field analysis (NTFA) and numerically high cost full‐field elasto‐plastic homogenization methods on the microscale. The present contribution deals with the application of the concept of downwind and upwind approximations to a goal‐oriented a posteriori error estimator based on duality techniques by means of reduced order homogenization schemes like NTFA, and with accuracy and numerical efficiency of the proposed goal‐oriented adaptive framework. NTFA consists of an offline phase and an online phase. During the offline phase, some relevant information of the micro system under consideration is precomputed allowing a reduced set of equations to be solved in the online phase. Thus, NTFA leads to a quite efficient homogenization method but less accurate compared to the full‐field homogenization method which is characterized with a high computational demand for accounting nonlinear microstructural mechanisms. Due to nonlinearities and time‐dependency of plasticity, the estimation of error transport and error generation are obtained with a backward‐in‐time dual method despite a high demand on memory capacity. In this contribution, the dual problem is solved with a forward‐in‐time dual method that allows estimating the full error during the resolution of the primal problem without the need for extra memory capacity. Several numerical examples illustrate the effectiveness of the proposed adaptive approach based on downwind and upwind approximations.

Uniaxial and biaxial experimental investigation of glassy polymers - Hamdoun, Ayoub; Mahnken, Rolf (Polymer)

A large deformation gradient theory for glassy polymers by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (Archive of Applied Mechanics)
Abstract Cold forming of polycarbonate films results in the formation of shear bands in the necking zone. The numerical results obtained from standard viscoplastic material models exhibit mesh size dependency, requiring mathematical regularization. For this purpose, we present in this work a large deformation gradient theory for a viscoplastic isotropic material model published before. We extend our model to a micromorphic model by introducing a new micromorphic variable as an additional degree of freedom along with its first gradient. This variable represents a microequivalent plastic strain. The relation between the macroequivalent plastic strain and the micromorphic variable is accomplished by a micromorphic coupling modulus. This coupling forces proximity between the macro- and microvariables, leading to the targeted regularization effect. The micromorphic model is implemented as a three-dimensional initial boundary value problem in an in-house finite element tool. The analysis is performed for both uniaxial and biaxial specimens. The provided numerical examples show the ability of our model to regularize shear bands within the specimens and address the issue of localization.

Downwind and upwind approximations for primal and dual problems of elasto-plasticity with Prandtl–Reuss type material laws - Mahnken, Rolf; Tchomgue Simeu, Arnold (Computer Methods in Applied Mechanics and Engineering)

Characterization of Interfacial Corrosion Behavior of Hybrid Laminate EN AW-6082 ∪ CFRP - Delp, Alexander; Wu, Shuang; Freund, Jonathan; Scholz, Ronja; Löbbecke, Miriam; Tröster, Thomas; Haubrich, Jan; Walther, Frank (Materials)
The corrosion behavior of a hybrid laminate consisting of laser-structured aluminum EN AW-6082 ∪ carbon fiber-reinforced polymer was investigated. Specimens were corroded in aqueous NaCl electrolyte (0.1 mol/L) over a period of up to 31 days and characterized continuously by means of scanning electron and light microscopy, supplemented by energy dispersive X-ray spectroscopy. Comparative linear sweep voltammetry was employed on the first and seventh day of the corrosion experiment. The influence of different laser morphologies and production process parameters on corrosion behavior was compared. The corrosion reaction mainly arises from the aluminum component and shows distinct differences in long-term corrosion morphology between pure EN AW-6082 and the hybrid laminate. Compared to short-term investigations, a strong influence of galvanic corrosion on the interface is assumed. No distinct influences of different laser structuring and process parameters on the corrosion behavior were detected. Weight measurements suggest a continuous loss of mass attributed to the detachment of corrosion products.

The new TISTRAQ process: Solution treatment with rapid quenching and annealing for Ti-6Al-4V sheet metal part forming - investigation on heat transfer coefficient and influence on cooling rates - Kaiser, Maximilian Alexander; Höschen, Fabian; Pfeffer, Nina; Merten, Mathias; Meyer, Thomas; Marten, Thorsten; Rockicki, Pawel; Höppel, Heinz Werner; Tröster, Thomas (IOM3. Chapter 14: Forming, Machining & Joining [version 1; not peer reviewed])
Within the current energy and environmental crisis, new material- and energy-saving processes are needed. For this reason, this study focuses on the development of a new forming technology for Ti-6Al-4V sheet metal. It is based on combination of solution treatment by resistive heating with rapid tool-based quenching and subsequent annealing. This new “TISTRAQ” process is comparable with press-hardening already known for steels and hot die quenching known for aluminium alloys. One of the main influencing factors for this process is the heat transfer coefficient (HTC). It is an important driver for adjustment of basic parameters, as selection of tool material or the forming speed but also plays an important role while elaborating temperature distribution in the numerical model. Therefore, a new and unique test rig was developed to determine the HTC and to perform tool-based heat treatment at specimen level under laboratory conditions. The test rig was used to investigate the influence of the titanium-tool-lubricant system on HTC and cooling rate. Further the effect of heat treatment in the test rig and tool-based quenching on microstructure and mechanical properties was studied. To improve the prediction of the temperature distribution of the titanium during cooling, the HTC was integrated into the numerical process simulation
Keywords: Interfacial heat transfer coefficient; Ti-6Al-4V; nonisothermal forming; thermomechanical processing; TISTRAQ process

The new TISTRAQ process: Solution treatment with rapid quenching and annealing for Ti-6Al-4V sheet metal part forming - the effect of processing parameters on microstructure and mechanical properties - Pfeffer, Nina; Kaiser, Maximilian Alexander; Meyer, Thomas; Göken, Mathias; Höppel, Heinz Werner (IOM3. Chapter 14: Forming, Machining & Joining [version 1; not peer reviewed])
The phase and TTT diagrams of the Ti-6Al-4V system allow the development of a new forming process for a more energy- and materialefficient production of sheet metal parts. This new “TISTRAQ” process is composed of two steps. In terms of process technology, the first step is comparable to a direct press-hardening process already well known for steels. In this step, the Ti-6Al-4V sheet material is resistively heated to a temperature below β-transus Tβ and, after a very short holding time, simultaneously formed and quenched by use of water cooled tools. Thereby, the β phase undergoes a martensitic transformation. The second step is a subsequent short-time annealing, which leads to a hardening of the material. In this work, a new test rig using resistive heating technique was used in order to produce different solution treated and tool quenched (STQ) and subsequently annealed (STA) states. In this paper, the effects of heating rate, solution treatment temperature and holding time on microstructure and mechanical properties are addressed. For the characterisation, tensile testing and scanning electron microscopy were used. By the systematic variation of applied processing parameters, dominating effects on microstructure and mechanical properties were evaluated. For example, the solution treatment temperature was found to have a significant effect on microstructural features and characteristic strength and strain values. The obtained results reveal a high potential for future technical applications.
Keywords: Ti-6Al-4V; thermomechanical processing; resistive heating; quench-forming; process parameter-microstructure-properties relationship

The Influence of Ultrasonic Irradiation of a 316L Weld Pool Produced by DED on the Mechanical Properties of the Produced Component - Lehnert, Dennis; Bödger, Christian; Pabel, Philipp; Scheidemann, Claus; Hemsel, Tobias; Gnaase, Stefan; Kostka, David; Tröster, Thomas (Crystals)
Additive manufacturing of metallic components often results in the formation of columnar grain structures aligned along the build direction. These elongated grains can introduce anisotropy, negatively impacting the mechanical properties of the components. This study aimed to achieve controlled solidification with a fine-grained microstructure to enhance the mechanical performance of printed parts. Stainless steel 316L was used as the test material. High-intensity ultrasound was applied during the direct energy deposition (DED) process to inhibit the formation of columnar grains. The investigation emphasized the importance of amplitude changes of the ultrasound wave as the system’s geometry continuously evolves with the addition of multiple layers and assessed how these changes influence the grain size and distribution. Initial tests revealed significant amplitude fluctuations during layer deposition, highlighting the impact of layer deposition on process uniformity. The mechanical results demonstrated that the application of ultrasound effectively refined the grain structure, leading to a 15% increase in tensile strength compared to conventionally additively manufactured samples.

Non-rotationally symmetric joints – Mechanisms and load bearing capacity - Devulapally, Deekshith Reddy; Martin, Sven; Tröster, Thomas (Materials Research Proceedings)
Abstract. Traditionally, joints are cylindrical and rotationally symmetric. In the present study, non-rotationally symmetric joints are used for joining steel and Glass mat-reinforced thermoplastic sheets (GMT). In addition, the study also analyzes the impact of non-rotational symmetric joint rotation on the load-bearing capacity. Single lap joint specimens were fabricated using the In-Mold assembly technique for joining steel sheets with GMT. Tensile shear tests were performed on different orientations of the joint geometry, and it was observed that changing the joint orientation influences the load-bearing capacity. The joints are constitutively modeled using beam elements and the influence of joint rotation on load distribution is examined through a static simulation study.

Process chain of a twin-roll cast aluminium-copper-lithium alloy - Mallow, Sina; Broer, Jette; Milkereit, Benjamin; Grydin, Olexandr; Hoyer, Kay-Peter; Garthe, Kai-Uwe; Milaege, Dennis; Boyko, Viktoriya; Schaper, Mirko; Kessler, Olaf (Production Engineering)
Abstract Rolling processes of conventional cast Al-Li alloys quickly reach their limits due to relatively poor material formability. This can be overcome by using twin-roll casting to produce thin sheets. Further thermomechanical treatment, including hot or cold rolling, and heat treatment can adjust the mechanical properties of twin-roll cast Al-Li sheets. The whole manufacturing chain requires detailed knowledge of the precipitation and dissolution behavior during heating, soaking and cooling, to purposefully select any process parameters. This study shows the process chain of a twin-roll cast Al–Cu–Li alloy achieving a hardness of around 180 HV1 by adapting the heat treatment parameters for homogenisation, hot rolling and age hardening. Both hardness and microstructure evolution are visualised along the process chain.

Comparative Analysis of Phase-Field and Intrinsic Cohesive Zone Models for Fracture Simulations in Multiphase Materials with Interfaces: Investigation of the Influence of the Microstructure on the Fracture Properties - Najafi Koopas, Rasoul; Rezaei, Shahed; Rauter, Natalie; Ostwald, Richard; Lammering, Rolf (Applied Sciences)
This study evaluates four widely used fracture simulation methods, comparing their computational expenses and implementation complexities within the finite element (FE) framework when employed on heterogeneous solids. Fracture methods considered encompass the intrinsic cohesive zone model (CZM) using zero-thickness cohesive interface elements (CIEs), the standard phase-field fracture (SPFM) approach, the cohesive phase-field fracture (CPFM) approach, and an innovative hybrid model. The hybrid approach combines the CPFM fracture method with the CZM, specifically applying the CZM within the interface zone. The finite element model studied is characterized by three specific phases: inclusions, matrix, and the interface zone. This case study serves as a potential template for meso- or micro-level simulations involving a variety of composite materials. The thorough assessment of these modeling techniques indicates that the CPFM approach stands out as the most effective computational model, provided that the thickness of the interface zone is not significantly smaller than that of the other phases. In materials like concrete, which contain interfaces within their microstructure, the interface thickness is notably small when compared to other phases. This leads to the hybrid model standing as the most authentic finite element model, utilizing CIEs within the interface to simulate interface debonding. A significant finding from this investigation is that within the CPFM method, for a specific interface thickness, convergence with the hybrid model can be observed. This suggests that the CPFM fracture method could serve as a unified fracture approach for multiphase materials when a specific interfacial thickness is used. In addition, this research provides valuable insights that can advance efforts to fine-tune material microstructures. An investigation of the influence of interfacial material properties, voids, and the spatial arrangement of inclusions shows a pronounced effect of these parameters on the fracture toughness of the material.

Holistische Methode zur elastischen Auslegung von geclinchten Bauteilen - Martin, Sven
Die Auslegung von gefügten Bauteilen ermöglicht die Produktion von Strukturbauteilen, welche teils aus sehr vielen Einzelteilen bestehen und durch eine hohe Anzahl von Fügepunkten verbunden sind. Die Eigenschaften der Einzelteile und die Prozessgrößen in der Fertigung unterliegen Schwankungen, die bei der Auslegung berücksichtigt werden müssen. Um diese Bauteile stets nach der Spezifikation zu liefern, werden die Prozesse gewöhnlich über die gesamte Prozesskette überwacht und das Bauteil überdimensioniert. Treten unvorhersehbare Störungen in der Prozesskette auf, kann das Bauteil nicht mehr weiter produziert werden. Entweder muss die Störung im Prozess behoben werden, was nicht immer möglich ist und die schon teils produzierte Charge muss vernichtet werden, oder der Teil der Prozesskette nach der Störung muss angepasst werden. Dies kann z.B. durch eine Änderungskonstruktion, wie der Anpassung der Fügepunktpositionen und der -anzahl, geschehen. In dieser Dissertation wurde eine Auslegungsmethode zur strukturellen elastischen Auslegung punktgefügter Bauteile entwickelt, mit der eine Anpassungskonstruktion, z.B. auf solche Störungen, möglich ist. Diese Methode basiert auf der Ausnutzung des Einflusses von geometrischen Bauteilgrößen, wie z.B. der Bauteildicke und der Fügepunktpositionierung, von veränderten Fügepunkteigenschaften sowie dem Verständnis zwischen Prozessgrößen und den erzeugten Fügepunkteigenschaften.

Prospective Life Cycle Assessment of Lightweight Structures in Vehicles for On-Demand Mobility Systems - Ostermann, Moritz; Marten, Thorsten; Tröster, Thomas (16th Biennial International Conference on EcoBalance)
Keywords: Life Cycle Sustainability Assessment; Prospective Life Cycle Assessment; Life Cycle Engineering; On-Demand Mobility; Mobility Services

Scenario-based life cycle assessment of vehicle lightweight structures - Ostermann, Moritz; Marten, Thorsten; Tröster, Thomas (Sustainability in Product and Production Engineering)

Stokes and anti-Stokes emission characteristics of Er3+/Yb3+ co-doped zinc tellurite glasses under 377 and 1550 nm excitations for solar energy conversion application - Suresh, Keenatampalle; Kesavulu, C.R.; Chalicheemalapalli Jayasankar, Deviprasad; Pecharapa, Wisanu; Kagola, Upendra Kumar; Tröster, Thomas; Jayasankar, C.K. (Journal of Luminescence)

Optical and photoluminescence characteristics of Pr3+-doped P2O5 +BaO+La2O3 glasses - Kesavulu, C.R.; Basavapoornima, Ch.; Ramprasad, Pikkili; Chalicheemalapalli Jayasankar, Deviprasad; Depuru, Shobha Rani; Jayasankar, C.K. (Chemical Physics Impact)

Praxisrelevante Aspekte des Stempelnietens für Organoblech-Metall-Hybridverbindungen - Moritzer, Elmar; Völklein, Paul Leonhard (DVS Sitzung FA11 - Kunststofffügen)

Werkstoffgerechte Auslegung von Direktverschraubungen in SMC/BMC Bauteilen - Moritzer, Elmar; Held, Christian (DVS Sitzung FA11 - Kunststofffügen)

Ambossfreies Ultraschallschweißen für nur einseitig zugängliche Schweißsituationen - Schöppner, Volker; Arndt, Theresa (DVS Plenarsitzung AG W4 Fügen von Kunststoffen)